Pengaruh Minat, Orang Tua, dan Penghargaan Finansial terhadap Pilihan Berkarier sebagai Konsultan Pajak - Cecilia Debora Salim (Journal of Business and Economics (JBE) UPI YPTK, 2019)
This study was to measure the effect of interest, parents, and financial rewards on the choice of a career as a tax consultant with accounting students' perceptions of tax brevet A and B as moderating variables. The population of 143 students majoring in accounting with a concentration of economics and business at UPI “YPTK” Padang class of 2018. Using probability sampling technique, with a sample of 59 people collected. The research instrument used in data collection is a questionnaire. The data analysis method used is multiple linear regression analysis method, using classical assumption test and hypothesis testing. The results showed: Interest has a positive and significant effect on career choice as a tax consultant, the influence of parents has no and no significant effect on career choice as a tax consultant, financial rewards have a positive and significant effect on career choice as a tax consultant